2008
DOI: 10.1007/s00299-008-0535-8
|View full text |Cite
|
Sign up to set email alerts
|

Hypocotyl-based Agrobacterium-mediated transformation of soybean (Glycine max) and application for RNA interference

Abstract: An efficient system of gene transformation is necessary for soybean [Glycine max (L.) Merrill] functional genomics and gene modification by using RNA interference (RNAi) technology. To establish such system, we improved the conditions of tissue culture and transformation for increasing the frequency of adventitious shoots and decreasing the browning and necrosis of hypocotyls. Adding N(6)-benzylaminopurine (BAP) and silver nitrate in culture medium enhanced the shoot formation on hypocotyls. BAP increased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 32 publications
0
41
0
1
Order By: Relevance
“…Shoot organogenesis of Gloxinia Sinningia speciosa Baill. has been enhanced by ethylene inhibitors 22 , and other studies confirmed that they improve shoot regeneration and transformation efficiency [23][24][25] . In this study, we developed an efficient method for the regeneration of P. tinctorium plants from internode explants by using different concentrations of an ethylene inhibitor and polyamine.…”
mentioning
confidence: 81%
“…Shoot organogenesis of Gloxinia Sinningia speciosa Baill. has been enhanced by ethylene inhibitors 22 , and other studies confirmed that they improve shoot regeneration and transformation efficiency [23][24][25] . In this study, we developed an efficient method for the regeneration of P. tinctorium plants from internode explants by using different concentrations of an ethylene inhibitor and polyamine.…”
mentioning
confidence: 81%
“…Embryonic tips were also found sensitive against kanamycin treatment at level higher then 10 mg/l. Addition of antioxidant in co-cultivation medium result in significant decrease in browning and necrosis of hypocotyls and increased GUS expression (Wang & Xu, 2008). Embryogenic tips showed better response for hypervirulent strain KYRT1 than EHA105 and LBA4404 when infected for 20 hours (Dang & Wei, 2007).…”
Section: Soybean Agrobacterium Mediated Transformationmentioning
confidence: 96%
“…However, conventional breeding is dependent on genetic resources, takes many years, and may be hindered by linkage drag in some instances (Boerma and Walker 2005). In contrast, RNAi-mediated gene silencing has been applied for modification of soybean seed components including enzymes and other proteins that are encoded by multiple gene copies (Chen et al 2006;Flores et al 2008;Nunes et al 2006;Schmidt and Herman 2008;Shi et al 2007;Wang and Xu 2008). RNAi, together with overexpression of exogenous or endogenous genes, is thus a powerful strategy for soybean improvement.…”
Section: Discussionmentioning
confidence: 99%